Do Specific Pedagogies and Problem-Based Teaching Improve Student Employability? A Cross-Sectional Survey of College Students - Li, Kerang; Peng, Michael Yao-Ping; Du, Zongmin; Li, Jing; Yen, Ke-Tien; Yu, Tsao (Frontiers in Psychology, 2020)
Higher education policy and manpower training fail to meet the requirement of rapidly-changing society and employers' expectation in Taiwan, resulting in the great gap between university education and employment. Students employability is also what all higher education institutions should focus whether a high degree of student learning outcomes can represent a high degree of students employability or not, this still unclarified. This study aims to explore the relationships among pedagogy for employability, problem-based teaching mode, absorptive capacity and student employability in higher education institutions (HEIs). In terms of analyzing a total sample of 553 undergraduates from 12 Taiwanese HEIs by using structural equation model (SEM), the results show that the influences of pedagogy for employability and problem-based teaching mode on absorptive capacity and student employability are statistically positive significant. Based on the findings, specific suggestions and managerial implications for HEIs, curriculum and instruction planning, and future research are provided.